Tribute to Tom Burns, 1959–2024 - Alicja Syska (Journal of Learning Development in Higher Education)
This paper pays tribute to Tom Burns as a distinguished and much-loved practitioner-scholar who dedicated his professional life to students and influenced colleagues in and beyond the Learning Development community. A loyal and supportive friend of our journal, Tom was a deeply admired teacher and mentor, a visionary and creative leader and writer, who on these pages is fondly remembered by his four colleagues: John Hilsdon, Debbie Holley, Sandra Abegglen, and Digby Warren. They offer personal recollections of his work and contributions to higher education, which are poetically spliced with editorial mediations that pay homage to Tom’s creative spirit.